Conducting research in real world settings—lessons learned from an implementation and process evaluation of Headsprout Early Reading® in special schools - Denne, Louise D.; Flynn, Samantha; Thompson, Paul A.; Morris, Rebecca; Roberts-Tyler, Emily J.; Hastings, Richard P.; Hayden, Nikita (Frontiers in Education, 2025)
BackgroundEvaluating the success of randomised controlled trials (RCTs) requires an understanding of the processes and experiences of those involved in implementation as much as an analysis of outcomes, particularly when conducted in real world settings. This implementation and process evaluation (IPE) explores the experiences of pupils and staff from special schools in England participating in an RCT examining whether Headsprout Early Reading® (HER®), an established on-line reading intervention shown to be effective at teaching early reading skills to pupils in mainstream schools, with additional support strategies and supervision, could be delivered successfully by school staff to pupils with intellectual disabilities.MethodsThe study used an embedded mixed methods approach within a RCT design, the results of which are reported elsewhere. It is the first study to include interviews with pupils with intellectual disabilities. With 55 schools (382 pupils in Key Stages 1 and 2) successfully recruited, it is also possibly the largest study of its kind to be conducted to date in special schools.ResultsIt was not possible for staff in the context at the time of the study (extreme pressures on staffing, meeting individual pupil needs, and pupil and staff absence, compounded by COVID-19) to comply with implementation and to deliver HER® to pupils with fidelity or to the dosage expected.ConclusionDespite implementation challenges, the study demonstrated an appetite among special schools to be included in research to find effective ways of teaching key skills to pupils with intellectual disabilities.